Acute health effects of desktop 3D printing (fused deposition modeling) using acrylonitrile butadiene styrene and polylactic acid materials: An experimental exposure study in human volunteers. (25th March 2018) - Gümperlein, I.; Fischer, E.; Dietrich‐Gümperlein, G.; Karrasch, S.; Nowak, D.; Jörres, R. A.; Schierl, R.
Abstract: 3D printers are increasingly run at home. Nanoparticle emissions from those printers have been reported, which raises the question whether adverse health effects from ultrafine particles (UFP) can be elicited by 3D printers. We exposed 26 healthy adults in a single‐blinded, randomized, cross‐over design to emissions of a desktop 3D printer using fused deposition modeling (FDM) for 1 hour (high UFP‐emitting acrylonitrile butadiene styrene [ABS] vs low‐emitting polylactic acid [PLA]). Before and after exposures, cytokines (IL‐1β, IL‐6, TNF‐α, INF‐γ) and ECP in nasal secretions, exhaled nitric oxide (FeNO), urinary 8‐isoprostaglandin F2α (8‐iso PGF2α ), and self‐reported symptoms were assessed. The exposures had no significant differential effect on 8‐iso PGF2α and nasal biomarkers. However, there was a difference ( P < .05) in the time course of FeNO, with higher levels after ABS exposure. Moreover, indisposition and odor nuisance were increased for ABS exposure. These data suggest that 1 hour of exposure to 3D printer emissions had no acute effect on inflammatory markers in nasal secretions and urine. The slight relative increase in FeNO after ABS printing compared to PLA might be due to eosinophilic inflammation from inhaled UFP particles. This possibility should be investigated in further studies using additional biomarkers and longer observation periods.